Infrared microspectroscopy analysis of Ibuprofen release from drug eluting beads in uterine tissue - Namur, J.; Wassef, M.; Pelage, J.P.; Lewis, A.; Manfait, M.; Laurent, A. (Journal of controlled release, 2009)
Ibuprofen loaded embolization beads (IBU-BB) have been developed to reduce inflammation and pain following uterine artery embolization for the treatment of uterine fibroids. The present work has investigated the elution properties of IBU-BB in situ after embolization with Fourier Transform Infrared Microspectroscopy (FTIRMS). Twelve sheep underwent uterine artery embolization with IBU-BB (485 mM) or control unloaded beads. IBU concentration was determined inside the beads and in the tissue surrounding the beads using FTIRMS of uterine tissue sections sampled 24 h or 1 week after embolization. After 24 h, IBU concentration inside the bead was only 18.6 mM out of the 485 mM initially loaded ( p < 0.0001, univariate sign test). The concentration in the tissue around the beads was 8 mM, which is well above the in vitro therapeutic levels (6 µM). After one week the concentration of IBU had decreased to 4.9 mM in the beads ( p = 0.0502, Mann Whitney) and no IBU was detected in the surrounding tissue. This work has demonstrated that IBU-BB can provide a sustained release of the anti-inflammatory drug over at least one week. The in vivo elution properties of IBU-BB may be suitable to alleviate pain and inflammation after embolization. [Display omitted]